Evaluación de los aprendizajes del bloque de álgebra y funciones en el rendimiento académico de los estudiantes de primero y segundo de bachillerato paralelos “a” de la unidad educativa Fernando Suárez Palacio de la ciudad de Loja; período académico 2018-2019. Lineamientos alternativos - Pacheco Tenesaca, Jackson Humberto (2019)
The purpose of this research is to determine the influence of the evaluation of learning in the study of the algebra block and functions in the academic performance of the first and second year high school students "A" of the Fernando Suárez Palacio Educational Unit, academic period 2018-2019. For the field research phase, a preliminary survey was made about the evaluation of learning and how it influences the academic performance of the students; For this, methods such as scientific, hypothetical - deductive, inductive - deductive, statistical, and techniques such as surveys, observations and the recording of grades were used, which allowed obtaining results and it was determined that the teacher of the subject manages to use an adequate evaluation of learning the topics of the algebra block and functions to achieve the development of knowledge, skills and abilities in the students, in addition, the academic performance of the students improved considerably obtaining a general average of 8.42 after the use of an adequate evaluation of learning , that is to say they reach the required learning and is slightly higher than the previous average, which allows to verify the hypothesis raised. From the results obtained it is concluded that students improve academic performance when the teacher uses a correct evaluation, so it is recommended that its application be adequate and timely in the classes of the algebra block and functions. Finally, an alternative proposal was presented, which consists of a didactic guide that includes the use of analytical and holistic rubrics to evaluate learning, activities to work in classes and skills plan with performance criteria, practical classes where it is sought that The student achieves a better understanding and assimilation of the contents of the block and thus improve their academic performance.